Reflections on the Voice : during and after the Campaign - Gunstone, Andrew (Arcadia, 2024)
For many decades, Indigenous peoples have been advocating to have a say on matters that impact upon their lives. On 14 October 2023, the Australian public voted in a Referendum on whether to enshrine a First Nations Voice to Parliament in the Constitution.